Low frequency noise analysis on Si/SiGe superlattice I/O n-channel FinFETs. (June 2020) - Boudier, D.; Cretu, B.; Simoen, E.; Hellings, G.; Schram, T.; Mertens, H.; Linten, D.
Abstract: Low frequency noise studies are performed in Si/SiGe superlattice I/O n-channel FinFETs. It was observed that the experimental noise spectra may contain additionally to flicker and white noise one or several generation recombination (GR) components. The methodology to estimate the noise parameters corresponding to the 1/ f noise and each GR noise contribution was detailed. It is found that the carrier number fluctuations mechanisms prevail the 1/ f noise. The important 1/ f noise level variability observed for devices having the same geometry may be related to the remote Coulomb scattering effect through the correlation between the mobility and the 1/ f noise levels. Low frequency noise spectroscopy was performed allowing to identify traps related to divacancies, hydrogen and a possible carbon contamination in Si/SiGe fins.